Pioneer and Reporter (2P) Training for the East Bintan District Children's Forum in Implementing Law Number 35 of 2014 Article 4 - Adiya Pepriyana; Novita Anggrainy; Suryaningsih (Jurnal Pengabdian Masyarakat Bestari, 2023)
This research aims to determine the aims and objectives of training for pioneers and reporters to the Children's Forum in the Implementation of Law Number 35 of 2014 Article 4 carried out by the Department of Women's Empowerment, Child Protection, Population Control and Family Planning, Bintan Regency. The method used in this research is qualitative with a descriptive presentation. The data sources used in this research are primary and secondary. Primary data sources were obtained from observations, documentation, and interviews conducted during training activities. This training was attended by Children's Forums from 4 sub-districts with 10 children each, and in this training, children were taught to have the courage to speak to the public, convey children's rights, explain cases of early marriage and bullying in their respective sub-districts and finally create a social mapping of their sub-district area.